TRENDS IN GREEN ACCOUNTING IN THE MODERN BUSINESS WORLD: A LITERATURE REVIEW ON ITS IMPLEMENTATION AND CHALLENGES - Chariya Maneekul (CV. Fahr Publishing, 2024)
This study aims to explore the trends, challenges, and adoption mechanisms of green accounting in the modern business environment, particularly within small and medium-sized enterprises (SMEs) and developing economies. Utilizing a structured literature review method, the research systematically analyzed 50 peer-reviewed journal articles published between 2015 and 2024. The findings reveal that while conceptual understanding of green accounting is growing, its practical implementation remains limited due to regulatory inconsistency, lack of standard reporting frameworks, and inadequate technological infrastructure. Larger firms and multinational corporations exhibit higher adoption rates driven by external pressure and compliance needs, whereas SMEs struggle due to limited resources and weak institutional support. The study contributes novelty by integrating the perspective of digital accounting systems—such as AI and blockchain—into the green accounting discourse, offering a more scalable and data-driven approach to environmental reporting. It also bridges the gap between financial and sustainability reporting by proposing a conceptual framework that combines regulatory, technological, and organizational factors influencing adoption. This research provides actionable insights for policymakers, educators, and practitioners seeking to advance environmental transparency in financial systems. In conclusion, green accounting holds substantial potential as a strategic sustainability tool, but its success depends on regulatory clarity, technological readiness, and tailored support for smaller enterprises. The study contributes both theoretically and practically by addressing under-researched contexts and offering directions for future empirical investigation.